2017
DOI: 10.1017/s1368980017003184
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding practices and dietary consumption of US infants and toddlers: National Health and Nutrition Examination Survey (NHANES) 2003–2012

Abstract: Objective: To compare infant and toddler anthropometric measurements, feeding practices and mean nutrient intakes by race/ethnicity and income. Design: Cross-sectional analysis using general linear modelling. Ten years of survey data (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) were combined to compare anthropometric measurements, feeding practices and mean nutrient intakes from a nationally representative US sample. Setting: The 2003-2012 National Health and Nutrition Examination Survey (NHANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…Mean energy intakes for age 0–11 mo, 12–23 mo, and 2–3 y were reported as 805 kcal/d, 1253 kcal/d, and 1461 kcal/d, respectively, in NHANES 2011–2014 (20), and 1335 kcal/d for 12–35-mo-olds in NHANES 2011–2012 (19). Energy intakes of 978 kcal/d were reported for 0–24-mo-olds in a combined data set from 2003–2012 NHANES (18), but we have found that energy intakes increase significantly across these ages, so we cannot compare them directly to our findings. We did not observe decreases in energy intake over time as was reported for 2–5-y-olds from NHANES between 1999–2000 and 2009–2010 (14).…”
Section: Discussionmentioning
confidence: 64%
“…Mean energy intakes for age 0–11 mo, 12–23 mo, and 2–3 y were reported as 805 kcal/d, 1253 kcal/d, and 1461 kcal/d, respectively, in NHANES 2011–2014 (20), and 1335 kcal/d for 12–35-mo-olds in NHANES 2011–2012 (19). Energy intakes of 978 kcal/d were reported for 0–24-mo-olds in a combined data set from 2003–2012 NHANES (18), but we have found that energy intakes increase significantly across these ages, so we cannot compare them directly to our findings. We did not observe decreases in energy intake over time as was reported for 2–5-y-olds from NHANES between 1999–2000 and 2009–2010 (14).…”
Section: Discussionmentioning
confidence: 64%
“…Vitamin B deficiencies are rare in infants [122]. Analyses from large dietary intake studies have found that most children aged 6-24 months are meeting recommendations for vitamins B6 [123,124], folate [124,125], and B12 [124] from food and supplements.…”
Section: B-vitaminsmentioning
confidence: 99%
“…The prevalence of vitamin A deficiency in the United States and other developed countries is low [110]. In a variety of recent NHANES analysis studies that looked at nutrient intakes in this age group, children ages 0-23.9 months were found to have mean food intakes of vitamin A near or in excess of the UL, ranging from 537.8 ± 7.4 to 675.4 ± 12.4 µg RAE per day [125,144,165]. A similar result was found for vitamin A intakes including foods, beverages and supplements [124].…”
Section: Vitamin Amentioning
confidence: 99%
See 1 more Smart Citation
“…Race is associated with breastfeeding rates in the United States. [1][2][3][4][5][6] Populations in the American South suffer from high rates of infant mortality 7,8 and chronic illness. [9][10][11] The South also has some of the nation's greatest racial and/or ethnic breastfeeding disparities.…”
mentioning
confidence: 99%